The rhetoric of leadership in the history of adult education: Implications for the acceptance of women as leaders - Melody M. Thompson (Adult Education Research Conference, 1993)
Although early histories of the field recognized women as leaders of adult education, later histories minimized or ignored their leadership activities. What have been the mechanisms of women's invisibility in adult education history? This study investigates issues of language and power that contribute to an understanding of this question.